Natural and anthropogenic uranium isotopes in a sediment core GeoB17409-1 from the Philippine Sea - Jixin Qiao; Peter Steier (PANGAEA, 2021)
Natural and anthropogenic uranium isotopes were determined in a sediment core GeoB17409-1. The age model was based on natural and artificial isotopes (Pittauer et al., 2017). 238U was determined by ICP-MS (ICP-QQQ 8800, Agilent). The ICP-MS instrument was equipped with an Xt-skimmer core and a concentric nebuliser under hot plasma conditions. The radiochemical method used for 233U and 236U determination in sediment was according to Qiao et al. (2015). 236U/238U and 233U/236U were measured by the accelerator mass spectrometry (AMS) by the 3-MV tandem accelerator facility VERA (Vienna Environmental Research Accelerator) at the University of Vienna, Austria (Qiao et al., 2022).